The effects of social variables on symptom recognition and medical care seeking behaviour for acute respiratory infections in infants in urban Mongolia. Issue 11 (1st July 2009) - Gombojav, N; Manaseki-Holland, S; Pollock, J; Henderson, A J
Abstract : Objective: To investigate potentially modifiable factors associated with carers' recognition of symptoms and timely presentation of infants with acute respiratory infections (ARI) in urban Mongolia. Methods: A prospective cohort study nested in a randomised controlled trial of infant swaddling. Data were collected on social, educational and childcare variables and all doctor contacts for ARI in primary and secondary care by regular questionnaires to carers of infants during the first 6 months of life. Findings: Analyses were based on 9024 ARI related doctor contacts for 4554 illness episodes in 1218 infants. Delay in medical care seeking (>3 days from acute lower respiratory infection (ALRI) symptom onset) was associated with younger maternal age (OR (95% CI) 3.8 (1.2 to 11.6)), single child families (3.8 (1.2 to 11.61)), absent father (4.1 (1.2 to 14.4)) and residence more than 1 km from a clinic (3.5 (1.2 to 10.2)). Conclusion: There is a continuing need to educate carers of infants in the management of ARI, particularly those of younger age and those with limited family support.